Shox2 and Rassf1a DNA methylation: diagnostic utility and association with clinical stage, histological progression and gene mutational landscape in lung adenocarcinoma - Li, Yixin; Zhang, Yangli; Alimu, Abida; Tan, Yulu; Zhang, Xiaojie; Xiang, Linguo; Li, Jia; Liu, Zhangling (Frontiers in Oncology, 2026)
BackgroundLung cancer, characterized by its high global incidence and mortality rates, necessitates comprehensive and precise stratification strategies to guide the diverse diagnostic approaches and therapeutic agents in clinical decision-making.ObjectivesShox2 and Rassf1a promoter methylation are established biomarkers for the early screening of lung cancer. This study comprehensively investigated the clinical utility of Shox2 and Rassf1a promoter methylation alongside driver mutations for molecular subtyping and stratification in 1027 lung adenocarcinoma (LUAD) patients.MethodsThis study included a cohort of 1027 LUAD patients who received treatment at the First Affiliated Hospital of Chongqing Medical University between January 2020 and August 2024. Comprehensive demographic and clinicopathological data were collected. Shox2 and Rassf1a methylation was quantified using the Lungme kit, while 10 driver mutations were detected by PCR assay. Chi-square tests were used to assess correlations between methylation status and clinicopathological characteristics; ROC analysis evaluated diagnostic performance for distinguishing LUAD subtypes. Multiple regression identified stage-associated hazardous factors.ResultsIn our cohort, Shox2 and Rassf1a methylation were correlated with more aggressive clinicopathological characteristics (age, sex, smoking, drinking, TNM stage and histological progression) and exhibited significant diagnostic potential for distinguishing early-stage lesions (adenocarcinoma in situ from LUAD across stages I-IV) and histological progression (minimally invasive adenocarcinoma versus invasive adenocarcinoma). Shox2 methylation exhibited significant co-occurrence with mutations of KRAS (p < 0.001) and MET (p = 0.02) and mutual exclusivity with mutations of EGFR (p < 0.001), RET (p = 0.013) and HER2 (p = 0.03). Rassf1a methylation showed no significant associations with these driver mutations. Combining Shox2 and Rassf1a methylation with EGFR mutations demonstrated enhanced discriminative capacity for early-stage lesions.ConclusionsOur study demonstrated that comprehensive analysis of methylation and gene mutations could provide a novel clinical strategy for molecular subtyping and precision medicine in LUAD.